The Role of Consumer Trust in Mediating Green Marketing and Word of Mouth Effects on Purchase Decision: The Moderating of Environmental Knowledge - Zahara Yulia; Sefnedi Sefnedi; Reni Yuliviona (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This study aims to analyze the effect of green marketing and word of mouth on purchase decision, with consumer trust as a mediating variable and environmental knowledge as a moderating variable, in the context of electric car consumers in West Sumatra Province. This study used a quantitative approach with primary data obtained through questionnaires from 134 respondents selected using cluster random sampling. Data analysis used Structural Equation Modeling (SEM) using Smart-PLS version 4. The results showed that green marketing and word of mouth did not have a significant influence on purchase decision. However, green marketing and word of mouth had a positive and significant influence on consumer trust. Furthermore, consumer trust and environmental knowledge had a positive and significant influence on purchase decision, and environmental knowledge had a positive and significant influence on consumer trust. In addition, the results of the study indicate that consumer trust mediates the relationship between green marketing and word of mouth on purchase decision. Meanwhile, environmental knowledge does not moderate the relationship between green marketing and consumer trust and does not moderate the relationship between consumer trust and purchase decision